Virtual Reality Improves The Knowledge of Midwives in IUD (Intra Uterine Device) Training - Intan Gumilang Pratiwi; Baiq Yuni Fitri Hamidiyanti; Achmad Arifin; Farid Husin; Rai Pandudita; Ristrini Ristrini; Adang Bachtiar; Gurendro Putro; Awan Dramawan; Maruni Wiwin Diarti (poltekkes kemenkes mataram, 2021)
IUD family planning users continue to decline from the 2012 IDHS as much as 4.9%, in 2017 IDHS data of 3.9%. The Total Fertility Rate (TFR) in NTB Province was 2.8 children higher than the national target of 2.36 children. This study aims to analyze the application of virtual reality technology to increase midwives' knowledge in installing IUD. The design of this research design is a quasi-experiment with a pre-post non-equivalent control group design. This research design uses two groups: the case group (the group that is given treatment or intervention using virtual reality) and the control group (the group that is not given treatment or not using virtual reality). The number of samples in this study was 30 respondents for each group (treatment and control). The results of this study that the average knowledge after the intervention group training has a higher average than the average in the control group with a p-value (0.000) <α (0.05).